HEALTH CONDITION OF THE FIRST YEAR INFANTS IN MIGRANT FAMILIES - V.Yu. Albitsky; N.D. Odinaeva; N.V. Nechaeva ("Paediatrician" Publishers LLC, 2006)
A complex clinical social study of health status, life style and conditions of infants aged 3 months to 1 year in migrant families living in Pushkino district of Moscow region for more than 2 years was carried out. The study has revealed that children in migrant families fall behind in physical development, most of them show a delay of psychomotor development, the level of revealed pathology is significantly higher vs. children of famia lies permanently residing in the area. The data acquired indicate the need of intent attention to the children in migrant families from both medical and social authorities. Key words: children, health status, physical development, children's condition.